Learning strategy training: Awakening students' awareness of learning strategy use - Bambang Sugeng (JOURNAL OF EDUCATION, 2008)
Abstract:  The study aimed at finding  out the impact of learning-strategy training in the instructionalprocess. English Department students of semester3 and 5 were given training in learning-strategy skills in a regular 16-week semester program. SILL (Oxford, 2000), modifiedfor thepurpose of the study, was administered on the first  day of class. Group and individual students' learning strategy profiles were examined for follow-up action plans. Strategy skills were integrated in the instructional material and activities. Students assigned themselves to strategy groups, for  example. Compensation group, and practiced the assigned skills. Weekly reflections were written by students reporting theirprogress in the use oflearning strategies and in their language learning. At the end of the semester, SILL was given for  the second time for reflective comparisons. Findings indicated that students (1) became aware of their learning strategies, (2) were more prepared for  and concentrated on instructional tasks, (3) had more positive attitude towardsforeign-language learning, and (4) improved their language learning.Keywords: learning strategies, learning strategy profile,  learning strategy skills, learning strategy use, learning strategy training